A review of seal killing practice in Europe: Implications for animal welfare. (December 2018) - Nunny, Laetitia; Simmonds, Mark P.; Butterworth, Andrew
Abstract: Seals are killed in a number of European countries and regions for commercial, management and recreational reasons. This is the first review to make a comparison across different nations, and it reveals that a variety of methods are employed, including the use of firearms, clubs, netting and harpoons. There is disparity in terms of which firearms and ammunition may be used and what, if any, training is required in killing methods. Seal killing presents serious animal welfare challenges and this may be exacerbated in some cases by the absence of close seasons, the practice of shooting from moving platforms or when conditions are suboptimal, and the use of nets. The introduction of internationally agreed standards could help ensure that welfare is paramount in seal management, legislation and practice. If lethal control measures are to continue, then good practice should include the annual training and assessment of hunters, the implementation and enforcement of relevant legislation, increased effort to improve the efficiency of killing (including the assessment of this through the expert and independent examination of carcasses), and minimising conflict by locating fish farms away from core seal habitat. Highlights: Many seals are deliberately killed in Europe each year by a variety of methods. These disparities are assessed regarding hunting efficiency and animal welfare. Some countries, including Scotland, do not specify close seasons to protect seals during breeding periods. Non-lethal deterrence measures and annual training of marksmen should be introduced throughout Europe. International standards for seal killing are advocated to help protect seal welfare.